A pathway towards the development and evolution of consumer behavior: Policy directions for sustainable development and improvement of nutrition - Su, Fang; Chang, Jiangbo; Zhang, Xing; Fahad, Shah; Aslam, Shimza Bint (Frontiers in Nutrition, 2022)
Introduction The virtuality, concealment, uncertainty and complexity of online trading make the online food trading market have security risks, while the lack of information, information asymmetry and imperfect market system make the “lemon problem” in the market increasingly obvious. Methods In order to clearly understand and manage the “lemon problem” in the online food trading market, we built an evolutionary game model involving the seller, buyers and online food trading platform, deeply analyzed the formation process of the “lemon problem” in the online food trading market, and revealed the influencing factors and effects of each subject’s strategy choice from the perspectives of subsidy, punishment, cost, and benefit. Results Findings of this study reveal that: (1) In the online food trading market, the strategy of the seller, buyer and platform will be stable in six situations, and the “lemon problem” will emerge with the development and evolution of the online food trading market. (2) The strategy of each subject in the online food trading market will be affected by variables like cost difference between positive performance and negative performance of the seller, punishment from the buyer with positive participation to the seller with negative performance, subsidy from the platform with positive regulation to the seller with positive performance, etc., and different factors have different influence directions and degrees on the subject strategy. (3) In the online food trading market, cost, punishment, subsidy and benefit have different effects on the subject’s strategy. Among them, cost and cost difference have the most significant impact on the subject’s strategy, followed by punishment and benefit difference, and subsidy and additional benefit have less impact on the subject’s strategy. Discussion Based on our study findings, it is proposed that by constructing a complete and standardized system of online food trading market from the aspects of examination and verification institution, reward and punishment institution, and supervision institution, it will be able to provide reference for managing the “lemon problem” in the online food trading market, promoting the sustainable development of the market, and ensuring the safety of online food.